Critical and Ideological Analysis of 1960s American Films : Análisis crítico e ideológico de películas estadounidenses de la década de 1960 - OMARI, K.A.; BANI-KHAIR, B.M. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACTThe films produced during the sixties of the twentieth century reflect the major events that took place during that period through indirect and implicit codes, symbols, cultural messages, and ideological thoughts. The use of symbolic and ideological messages and suggestive scenes accentuates the complexity of understanding those films critically and historically. This paper critically studies the profound cultural and ideological meanings and messages of some representative key films of the 1960s in America, such as Hitchcock’s Marnie (1964), John Schlesinger’s Midnight Cowboy (1969), and Dennis Hopper’s Easy Rider (1969). RESUMENLas películas producidas durante los años sesenta del siglo XX reflejan los principales acontecimientos que tuvieron lugar durante ese período a través de códigos indirectos e implícitos, símbolos, mensajes culturales y pensamientos ideológicos. El uso de los mensajes simbólicos e ideológicos y las escenas sugerentes acentúa la complejidad de entender esas películas crítica e históricamente. Este artículo estudia críticamente los profundos significados culturales e ideológicos y los mensajes de algunas películas clave representativas de la década de 1960 en Estados Unidos, como Marnie de Hitchcock (1964), Midnight Cowboy de John Schlesinger (1969) y Easy Rider (1969) de Dennis Hopper.